2010
DOI: 10.1371/journal.pone.0009495
|View full text |Cite
|
Sign up to set email alerts
|

CNTF Induces Regeneration of Cone Outer Segments in a Rat Model of Retinal Degeneration

Abstract: BackgroundCone photoreceptors are responsible for color and central vision. In the late stage of retinitis pigmentosa and in geographic atrophy associated with age-related macular degeneration, cone degeneration eventually causes loss of central vision. In the present work, we investigated cone degeneration secondary to rod loss in the S334ter-3 transgenic rats carrying the rhodopsin mutation S334ter.Methodology/Principal FindingsRecombinant human ciliary neurotrophic factor (CNTF) was delivered by intravitrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 38 publications
(40 reference statements)
8
118
0
3
Order By: Relevance
“…Together, these data suggest that the increased retinal thickness reflects increased photoreceptor metabolic activity or an increased number of photoreceptors. Consistent with these findings, CNTF was recently shown to prolong cone photoreceptor survival and regenerate cone outer segments in a rat model of retinal degeneration (24). In this study, the CNTF cone rescue was most effective during early stage of the disease when the loss of cones was incomplete.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Together, these data suggest that the increased retinal thickness reflects increased photoreceptor metabolic activity or an increased number of photoreceptors. Consistent with these findings, CNTF was recently shown to prolong cone photoreceptor survival and regenerate cone outer segments in a rat model of retinal degeneration (24). In this study, the CNTF cone rescue was most effective during early stage of the disease when the loss of cones was incomplete.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the CNTF cone rescue was most effective during early stage of the disease when the loss of cones was incomplete. Once complete cone loss had occurred during late stage of disease, CNTF could no longer bring the cone receptors back, suggesting the importance of early treatment (24). Consistent with observations in the animal studies, using adaptive optics scanning laser ophthalmoscopy (AOSLO), Talcott et al (25) recently reported cone preservation in CNTF-treated eyes compared with the sham-treated fellow eyes in patients with retinitis pigmentosa and Usher Syndrome Type 2.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, spatial and temporal control of transgene expression could be mediated by a second AAV vector expressing, for example, inducible Cre recombinase (Li et al, 2006). In the case of therapies for mendelian diseases in which the underlying mutation is unknown, a combination therapy of antioxidants and/or growth factors may prolong cell survival and function (Komeima et al, 2007;Yang et al, 2009;Li et al, 2010). To treat patients with retinal degenerations it is possible that multivalent therapeutic strategies may be required.…”
Section: Discussionmentioning
confidence: 99%
“…Interessanterweise scheint CNTF seine protektive Wirkung indirekt über Müller-Gliazellen zu entfalten. CNTF ist vor allem deshalb interessant, weil der Faktor neben Stäb-chen auch Zapfen schützen kann und zudem die Regeneration der Zapfenaußensegmente fördert [27]. Vor diesem Hintergrund ist CNTF auch in Bezug auf den klinischen Einsatz attraktiv.…”
Section: Neurotrophe Faktorenunclassified